(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Unanticipated difficult laryngoscopy remains an important contributor to airway-related morbidity. Conventional bedside tests such as Modified Mallampati class, thyromental distance, sternomental distance and neck circumference are useful but imperfect predictors. Airway ultrasonography offers a portable, non-invasive method for objective assessment of anterior neck and tongue-related airway anatomy.123 Objective: To evaluate the role of airway ultrasound in predicting difficult laryngoscopy and compare its diagnostic performance with conventional airway assessment tests. Methods: This prospective observational analytical study was designed among 60 adult ASA I-II patients undergoing elective surgery under general anaesthesia requiring endotracheal intubation. Preoperative assessment included Modified Mallampati class, thyromental distance, sternomental distance, inter-incisor gap and neck circumference. Ultrasound parameters included skin-to-hyoid bone distance, skin-to-thyrohyoid membrane distance, distance from skin to epiglottis and tongue thickness. Direct laryngoscopic view was graded using the Cormack-Lehane system. Grades I-II were considered easy laryngoscopy and Grades III-IV as difficult laryngoscopy. Results: Difficult laryngoscopy was observed in 9 of 60 patients (15.0%). Patients with difficult laryngoscopy had significantly higher neck circumference, higher Mallampati class, shorter thyromental and sternomental distances, and greater ultrasound-measured anterior neck soft tissue thickness. Among ultrasound variables, distance from skin to epiglottis showed the highest discrimination (AUC 0.86), followed by tongue thickness (AUC 0.82) and skin-to-hyoid distance (AUC 0.78). A combined model using Mallampati class, thyromental distance and distance from skin to epiglottis achieved an AUC of 0.91. Conclusion: Airway ultrasound, particularly measurement of skin-to-epiglottis distance and tongue thickness, showed better predictive performance than individual conventional bedside tests in this dataset. Incorporating ultrasound into routine pre-anaesthetic airway assessment may improve identification of patients at risk of difficult laryngoscopy.